FEATURES OF THE CYTOKINE PROFILE AND CHARACTERISTICS OF CLINICAL VARIANTS OF JUVENILE IDIOPATHIC ARTHRITIS IN CHILDREN (International journal of medical sciences, 2026)
The article describes the clinical and immunological features of juvenile idiopathic arthritis and the consequences of the disease after treatment. Clinical features of the disease, laboratory analysis results are important when choosing an effective treatment method. An effective treatment method is characterized by a faster onset of remission, prolongation of its duration and reduction of side effects of drug treatment.